LAPSE OF DIGNITY IN CARE IN THE HOSPITALISED ELDERLY: A FIELD STUDY FROM NAGPUR CITY - Poorvaali Sur (Ageing and society: The Indian journal of gerontology, 2014)
A Study on lapse in dignity of care of elderly in a hospitalised Indian setting was conducted. Total of four case studies were selected after performing abbreviated mental test score on them to rule out cognitive impairment. In one case both patient and relatives gave narrations. This study was only one of its kinds, as no Indian studies were found in this direction. Study also revealed, lack of a structured geriatric care in India, including lack of a political/organisational will in the direction, and the lack of in house protocols for elder care. The study also points to suggest further studies, in this direction to find out what is undignified to our elder population and the need for more carer versions studies and analysis to make and support robust elder care bundles and deliver them in a Dignified manner. The domains selected for conducting the study as being most closely appropriated to the Indian setting were, eating and nutrition, autonomy, privacy, confidentiality, personal hygiene,communication, pain, physical restraint and manual handling.